Synthesis and characterization of low dimensional and heterostructure magnetic quantum and nanostructure materials prepared using electrodeposition method - Rokh, Ghazaleh Bahman (2016)
Low dimensional structures such as nanowires, thin films and hetreostructures have attracted considerable attraction in advanced electronic devices since they exhibit diverse and interesting physical phenomena compared with bulk structures. One of the most rapidly growing fields in electronics is spintronics which combines both the spin and charge of the electrons. Compared with conventional semiconductors, dilute magnetic semiconductors (DMSs) offer better performance for new generation devices. For this purpose, group II-VI semiconductors of ZnSe and ZnS and dilute magnetic semiconductors of (Zn,Mn)Se and (Zn,Mn)S were chosen as the materials in this research. The incorporation of magnetic manganese ions in semiconductor ZnSe and ZnS structures was the source of spin-polarized electrons. Highly technological low dimensional systems are fabricated by expensive and sophisticated methods such as molecular beam epitaxy. The problem is that the synthesis method for fabrication of such structures is very expensive. Our main attempt is to solve this problem by applying inexpensive and easy synthesis method like electrodeposition for preparation of low dimensional and heterostructures. The properties of thin films, heterostructures and nanowires were studied by applying various characterization methods. The XRD results showed formation of highly crystallined ZnSe and ZnS thin films and the crystallinity increased at lower deposition temperatures. All deposited thin films showed mixed cubic a hexagonal structures. XRD results of Mn doped ZnSe and ZnS thin films indicated well doped samples that perfectly matched with Zn1-xMnxSe and Zn1-xMnxS (x = 0.01, 0.05 and 0.1).. The calculated strain and dislocation density from XRD data showed a gradual increase with increasing manganese concentration. FESEM images showed that films cover perfectly the surface of ITO substrate. In addition no defects or cracks were observed on the surface of the thin films. The optical measuremets indicated that with increasing grain size and film thickness the absorption edge shifted to higher wavelengths and a red shift is observed in bandgap. The grain size and film thickness were increased with increasing deposition temperature and deposition time. Mn doped thin films revealed a red shift with increasing manganese concentration. Very high bandgap for both semiconductor and dilute magnetic semiconductors were obtained and the bandgap blue shifted compared with bulk ZnSe and ZnS. Photoluminescence spectra for semiconductor and DMS thin films were obtained and the results showed a characteristic strong green emission peak centred at 440 nm (2.82 eV) for ZnSe. Mn-doped ZnSe systems showed a dominant yellow/orange emission present at 599 nm which results from the 4T1-6A1 transition of the Mn2+ impurity excited by energy transfer from the host ZnSe lattice. The blue emission at 376 nm (3.28 eV) is obtained for ZnS thin films that attributed to surface states. The non-ohmic I-V characteristic was observed for ZnSe and ZnSe-Mn thin films. With increasing Mn concentration in ZnSe thin films the resistivity dereased. In addition the resistivity decreased with increasing the film thickness. Moreover, ZnS and ZnS thin films doped with Mn revealed ohmic behaviour. In ZnS thin films the resistivity increased as the film thickness increased. More doping leads to higher conductivity in ZnS-Mn thin films. Single quantum well ZnSe/(Zn,Mn)Se and ZnS/(Zn,Mn)S heterostructures prepared by electrodeposition method. The thickness of quantum wells increased with increasing the deposition time. The variation in bandgap between the layers of heterostructures is invesitaged. The bandgap differences between barrier and quantum well materials were in the range of 100-300 meV. The quantum mechanical tunnelling and transport properties were investigated by photoluminescence, 2-point probe and electron spin resonance data. The amount of tunnelling and spin transport strongly depended on the quantum well thickness as well as the concentration of Mn in the barrier. ZnSe, ZnS and Mn doped nanowires embedded in polycarbonate membranes revealed an increase in optical and electrical properties with decreasing the pore diameter. The higher bandgap was obtained in nanowires with smaller diameters. In addition the bandgap enhanced with increasing Mn concentration in nanowires. High resistivity and low conductivity was observed for nanowires with larger diameters.